Galaxy Zoo: Dust and molecular gas in early-type galaxies with prominent dust lanes - Kaviraj, S; Ting, Y; Bureau, M; Shabala, S; Crockett, R; Silk, J; Lintott, C; Smith, A; Keel, W; Masters, K; Schawinski, K; Bamford, S (2012)
We explore the properties of dust and associated molecular gas in 352 nearby (0.01 < z < 0.07) early-type galaxies (ETGs) with prominent dust lanes, drawn from the Sloan Digital Sky Survey (SDSS). Two-thirds of these 'dusty ETGs' (D-ETGs) are morphologically disturbed, which suggests a merger origin, making these galaxies ideal test beds for studying the merger process at low redshift. The D-ETGs preferentially reside in lower density environments, compared to a control sample drawn from the general ETG population. Around 80per cent of D-ETGs inhabit the field (compared to 60per cent of the control ETGs) and less than 2per cent inhabit clusters (compared to 10per cent of the control ETGs). Compared to their control-sample counterparts, D-ETGs exhibit bluer ultraviolet-optical colours (indicating enhanced levels of star formation) and an active galactic nucleus fraction that is more than an order of magnitude greater (indicating a strikingly higher incidence of nuclear activity). The mass of clumpy dust residing in large-scale dust features is estimated, using the SDSS r-band images, to be in the range 10 4.5-10 6.5M ⊙. A comparison to the total (clumpy + diffuse) dust masses - calculated using the far-infrared fluxes of 15per cent of the D-ETGs that are detected by the Infrared Astronomical Satellite (IRAS) - indicates that only 20per cent of the dust is typically contained in these large-scale dust features. The dust masses are several times larger than the maximum value expected from stellar mass loss, ruling out an internal origin. The dust content shows no correlation with the blue luminosity, indicating that it is not related to a galactic scale cooling flow. Furthermore, no correlation is found with the age of the recent starburst, suggesting that the dust is accreted directly in the merger rather than being produced in situ by the triggered star formation. Using molecular gas-to-dust ratios of ETGs in the literature, we estimate that the median current molecular gas fraction in the IRAS-detected ETGs is ∼1.3per cent. Adopting reasonable values for gas depletion time-scales and starburst ages, the median initial gas fraction in these D-ETGs is ∼4per cent. Recent work has suggested that the merger © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.